The Influence of Competence And Work Motivation on Nurses' Performance at RSI Siti Aisyah Madiun - Amalus Sholeha Abdi Priyanti; Riska Ratnawati; Avicena Sakufa (Green Publisher Indonesia, 2024)
The declining performance quality among inpatient nurses at RSI Siti Aisyah Madiun can be attributed to various risk factors, including their competency and work motivation in terms of knowledge and skills. This research aimed to assess how competency and work motivation influence nurse performance at the hospital. Employing a quantitative approach with a cross-sectional design, the study included all inpatient nurses from RSI Siti Aisyah Madiun over the past year, totaling 40 respondents, with 36 participating as the sample. Data collection utilized questionnaires, and analysis employed Chi-Square tests. The findings indicated significant influences: competence showed a notable impact on nurse performance (p-value = 0.024, OR = 7.286, 95% CI = 1.508-35.211), highlighting it as a crucial factor affecting nurse performance. Similarly, work motivation also significantly influenced nurse performance (p-value = 0.009, OR = 8.800, 95% CI = 1.920-40.336). In conclusion, this study underscores the pivotal role of both competence and work motivation in shaping nurse performance at RSI Siti Aisyah Madiun. The study recommends that the hospital enhance nurse competency and work motivation to ensure the delivery of optimal healthcare services.